Anti-inflammatory Activity Test of Red Pucuk Leaf Extract Against (Syzygium myrtifolium Walp) White Rats (Rattus norvegicus) - Ona Bugis Tehuayo; Angga Bayu Budiyanto; Irwandi Irwandi (Sean Institute, 2026)
The plant S. myrtifolium Walp, also known as red shoots, is an ornamental plant with characteristic red easy leaves and green old leaves. This plant is known to contain active compounds that have potential as pharmacological agents, especially anti-inflammatory. The purpose of this study was to identify the anti-inflammatory activity of ethanol extract of red shoot leaves (S. myrtifolium Walp) against white rats (Rattus norvegicus) using several dose variations. The population in this study was the red shoots leaf plant (Syzygium myrtifolium Walp) obtained from Mariat Pantai Village, Sorong Regency. While the samples used in this study were red shoot leaves (Syzygium myrtifolium Walp) which were taken fresh green leaves. The results of phytochemical analysis identified the presence of alkaloid, flavonoid, tannin, saponin and phenol compounds. The test data were analyzed using ANOVA method followed by Paired Sample T test and LSD test to determine the presence and absence of differences from before treatment and after treatment. The test results showed that red shoot leaf extract has anti-inflammatory activity against white rats significantly at doses of 200 mg / kg BW, 300 mg / kgBB and 450 mg / kgBB.